Investigation of volute geometry on pressure distribution in impeller casing - Hu, Wei (2008)
The present work focuses on the investigation of the effect of the volute geometry, especially, the volute profile, radial clearance and volute tongue position on the circumferential pressure distribution and the magnitude of imbalanced radial force. A series of volute models were designed based on two volute design methods.